Needs Analysis of the Development of Interactive Multimedia Containing the Character of Pancasila Students Profile in Pancasila Education Subjects in Elementary Schools - Fatonah, Atiek Sari; Chotimah, Umi; Maharani, Siti Dewi (Journal of English Language and Education, 2025)
This study aims to explore the need for the development of interactive multimedia with the character of the Pancasila Student Profile in the subject of Pancasila Education in elementary schools. The method used was descriptive qualitative approach with need assessment, involving teachers, students, principals, and supervisors. The results showed that the majority of teachers still use conventional methods and are less familiar with interactive technology. Meanwhile, a questionnaire to students indicated the level of difficulty in understanding the material, as well as the need for interesting and effective learning media. This study concludes that there is an urgent need to develop interactive multimedia that can support relevant and enjoyable learning experiences, in order to improve the understanding and internalization of Pancasila values in students' daily lives.